POLA PEMELIHARAAN IDENTITAS ETNIK (Studi tentang Komunitas Bali di Kepenghuluan Pasir Putih Kecamatan Bagan Sinembah Kabupaten Rokan Hilir) - Astuti, Dwi Windri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
Community etnhic Bali is Balinese population mobility in 1962 to the North Sumateraregion through a rubber plantation company and ended his tenure in 1979. In 1988 until1989 most people Bali descendants migrated to Riau region, preasury in Pasir Putih village,Bagan Sinembah district. Some communities immigrants and discendants of the relativelysmall of people survival strategis as a newcomer to this day. To analyze the data andresearch conducted with qualitative methods. This research make the entire population as asubject of research plus two key informants. This research conducted in the Kampung Balilocated in RT 01 RW 02 Dusun Sumber Makmur, Pasir Putih village. The research revealedthe social system and adaptation communities ethnic Bali. system social of ethnic Bali inKampung Bali is complete unity. Specifically: confidence and knowledge, feelings, goals,positions and roles, norm, level and rank, power, facilities and infrastucture. The elementsare interconnected to form an orderly society. Adaptation known though culture systems,such as tools and equipment life, livelihood and economics system, social systems, kinshipssystem, political systems, languages, arts, religion systems and knowledge systems. Identityethnic Bali in Bagan Sinembah make the identities are traditional measure of society. Inaddition to the original identity of the Balinese people, also formed a new identity after livingin the area Bagan Sinembah. The identity is an adaptation to region they in habbit today.Key words : maintanance of identity, community, adaptation, ethnic Bali